2019
DOI: 10.4414/smw.2019.20035
|View full text |Cite
|
Sign up to set email alerts
|

Negligible impact of highly patient-specific decision support for potassium-increasing drug-drug interactions – a cluster-randomised controlled trial

Abstract: BACKGROUND AND OBJECTIVE: Clinical decision support (CDS) might improve management of potassium-increasing drug-drug interactions (DDI). We studied CDS with five features intended to increase effectiveness: (i) focus on serious DDIs, (ii) fewer notifications, (iii) presentation of current laboratory results, (iv) timing (when adverse event becomes likelier), (v) removal of notification when appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Optimization strategies for monitoring prescribed medications attempted to identify and reduce adverse drug reactions 40 or drug-drug interactions. 39 , 40 In 1 study, CDS was combined with pharmacogenetic data to help identify drug therapy problems in polypharmacy patients, 40 whereas in another study, 5 features of an existing CDS were optimized to deliver patient-specific decision support for potassium-increasing drug-drug interactions. Neither of these studies were reported as having a positive effect on their respective primary end points.…”
Section: Resultsmentioning
confidence: 99%
“…Optimization strategies for monitoring prescribed medications attempted to identify and reduce adverse drug reactions 40 or drug-drug interactions. 39 , 40 In 1 study, CDS was combined with pharmacogenetic data to help identify drug therapy problems in polypharmacy patients, 40 whereas in another study, 5 features of an existing CDS were optimized to deliver patient-specific decision support for potassium-increasing drug-drug interactions. Neither of these studies were reported as having a positive effect on their respective primary end points.…”
Section: Resultsmentioning
confidence: 99%
“…However, when the side effects were low (p value = 0.02), it had effects on the continuous use of the medication. In addition, text messages had an effect on the physicians' knowledge in using medication with fatty foods (p value<0.0001) [59].…”
Section: The Effect Of Cdss On Malariamentioning
confidence: 98%
“…[49]; Avansino et al [51], and Bruxvoort et al [59]. Because of the limited number of patients in these trials, we decided to exclude them from our meta-analysis.…”
Section: Statistical and Sensitivity Analysismentioning
confidence: 99%
“…Thus, patient safety could be increased [48]. In another study, the time lapse in hyperkalemia monitoring (p-value=0.20) and the incidence rate of hyperkalemia (p-value=0.22) did not differ significantly even with use of three different kind of reminder and alert based CDSSs [49]. Table 11 shows the result briefly.…”
Section: The Effect Of Cdss On Increasing Blood Potassiummentioning
confidence: 99%